2021
DOI: 10.1007/s10798-021-09678-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of preschool technology education: analyses of seven individual preschool teachers’ and childcare attendants’ descriptions of their teaching

Abstract: In recent decades the preschool has leaned more towards a learning-oriented pedagogy, where the subject of technology has been given a more prominent place. Still, studies on how individual preschool staff members perceive and teach technology is scarce. This study shows how seven preschool staff in Sweden describe their work with the subject of technology and how technology education is characterized in these descriptions. The data was produced by means of semi-structured interviews and a questionnaire and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A case study conducted by Mawson (2013) concerning 3-4-year-old children's technological experiences in early childhood settings in New Zealand indicated that children developed a higher level of understanding of the technological process in an activity when the activities were planned and organised by the teacher. Some recent studies from Sweden (Sundqvist, 2020(Sundqvist, , 2021Thorshag & Holmqvist, 2019) emphasise that in play-based collaborative learning activities, the teacher's role is crucial, since how technological knowledge is mediated by teachers in such activities is imperative for the kind of technological knowledge that is made available for the children to develop. On the same note, the findings of an observational study by Johansson (2020) involving a Swedish preschool class indicate the importance of directing the children's focus to the companion meanings (described as value judgements on what knowledge is and what kind of knowledge is worth knowing) as means for teachers to organise technology education.…”
Section: Childrenteachers and In Situ Technology Activities In Preschoolmentioning
confidence: 99%
“…A case study conducted by Mawson (2013) concerning 3-4-year-old children's technological experiences in early childhood settings in New Zealand indicated that children developed a higher level of understanding of the technological process in an activity when the activities were planned and organised by the teacher. Some recent studies from Sweden (Sundqvist, 2020(Sundqvist, , 2021Thorshag & Holmqvist, 2019) emphasise that in play-based collaborative learning activities, the teacher's role is crucial, since how technological knowledge is mediated by teachers in such activities is imperative for the kind of technological knowledge that is made available for the children to develop. On the same note, the findings of an observational study by Johansson (2020) involving a Swedish preschool class indicate the importance of directing the children's focus to the companion meanings (described as value judgements on what knowledge is and what kind of knowledge is worth knowing) as means for teachers to organise technology education.…”
Section: Childrenteachers and In Situ Technology Activities In Preschoolmentioning
confidence: 99%